2013
DOI: 10.1002/adma.201300929
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Redox Heterogeneity‐Responsive Prodrug Nanocapsules for Cancer Chemotherapy

Abstract: A prodrug forms nanocapsules responsive to tumor GSH/ROS heterogeneity releasing the parent drug SN38 via thiolysis in the presence of GSH (glutathione) or via enhanced hydrolysis due to ROS (reactive oxygen species)-oxidation of the linker, giving rise to high in vitro cytotoxicity and in vivo anticancer therapeutic activity. The nanocapsules are a suitable size for tumor targeting by means of the EPR effect and have a fixed SN38 loading content of 35 wt%, ideal for translational nanomedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
284
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(292 citation statements)
references
References 44 publications
4
284
1
3
Order By: Relevance
“…However, most hydrophobic chemotherapeutics alone cannot self-assemble into stable nanoprecipitates in aqueous media without the help of adjuvant matrices. By exploiting the innate hydrophobicity of therapeutics, various amphiphilic prodrugs covalently coupled with hydrophilic motifs [e.g., oligo(ethylene glycol) (17)(18)(19), polypeptides (20,21), and copolymers (22)(23)(24)(25)] have been leveraged to mimic the self-assembly behavior that ubiquitously occurs in nature. More intriguingly, several groups, including us, have recently demonstrated that the attachment of lipophilic moieties to anticancer agents conferred the prodrug amphiphiles with the ability to form colloidally stable nanoaggregates rather than precipitants, despite the enhanced overall lipophilicity of prodrugs (26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…However, most hydrophobic chemotherapeutics alone cannot self-assemble into stable nanoprecipitates in aqueous media without the help of adjuvant matrices. By exploiting the innate hydrophobicity of therapeutics, various amphiphilic prodrugs covalently coupled with hydrophilic motifs [e.g., oligo(ethylene glycol) (17)(18)(19), polypeptides (20,21), and copolymers (22)(23)(24)(25)] have been leveraged to mimic the self-assembly behavior that ubiquitously occurs in nature. More intriguingly, several groups, including us, have recently demonstrated that the attachment of lipophilic moieties to anticancer agents conferred the prodrug amphiphiles with the ability to form colloidally stable nanoaggregates rather than precipitants, despite the enhanced overall lipophilicity of prodrugs (26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] In recent studies, the potential applications of poly(propylene sulfi de)-based nanomaterials have been evaluated. [ 20 ] Zhu and co-workers reported an anticancer nanomicelle system based on H 2 O 2 -responsive hyperbranched polymers [ 21 ] A hydrophobic anticancer drug, 7-ethyl-10-hydroxy-camptothecin (SN38), was conjugated onto hydrophilic hyperbranched polyglycerol (HPG) via thioether linkage. The thioether was easily oxidized into hydrophilic sulfone or sulfoxide, leading to the breakdown of phenol ester of SN38.…”
Section: Thioether-containing Polymersmentioning
confidence: 99%
“…Poly(propylene sulfi de) [19][20][21][22] Selenium-containing polymers [26,28,29] [ 25,30] Telluriumcontaining polymers [35][36][37] Poly(thioketal) [38][39][40]46] [ [41][42][43][44][45]55] Phenylboronic acid/ ester containing polymers Poly(L-methionine) [49] Poly(L-proline) [53,54] Macromolecular Bioscience www.mbs-journal.de and SN38 resulted in enhanced proliferation inhibition of tumor cells via inducing cell apoptosis. In addition to drug carrier, the thioether-containing particles themselves can also show inherent therapeutic properties against oxidative stress.…”
Section: Chemical Structure and Oxidation Referencesmentioning
confidence: 99%
“…Using bio-inspiration from the antimalarial mechanism of ART in nature, here we explored methemoglobin (MHb)-an oxidized form of hemoglobin with iron in the ferric state (Fe 3+ ) rather than in the ferrous state (Fe 2+ )-as a smart nanocarrier for hydrophobic ART. While MHb reacts very slowly with ART, 14,15 the upregulated reducing capacity [16][17][18][19] of the tumor tissue can work as an excellent biogenic trigger to reduce ferric iron in MHb to the ferrous state, activating its ability to generate free radicals and resulting in the cytotoxicity of ART in situ (Scheme 1).…”
Section: Artemisinin (Art) Was Acknowledged With the 2015 Nobel Prize Inmentioning
confidence: 99%